PENGARUH KOMPENSASI DAN BUDAYA KERJA TERHADAP KINERJA KARYAWAN BURGER KING STORE AREA BK86 - Rafiq Ramadhan; Arry Dwi Syahputra (Jurnal Ekonomi dan Industri, 2023)
To determine the effect of compensation and work culture on employee performance at Burger King Store area BK 86. This research is included in the category of causal associative research using a quantitative approach. The research was conducted by distributing questionnaires to respondents and all of them were employees at Burger King Store Pondok Bambu and Burger King Store Lagoon Avenue, the research method used multiple and simple linear regression analysis. The results of the study stated that compensation and work culture in multiple and simple ways had a positive effect on the performance of Burger King Store employees in the BK 86 area.